2019
DOI: 10.1111/apa.14833
|View full text |Cite
|
Sign up to set email alerts
|

Five‐year survival of infants with major congenital anomalies: a registry based study

Abstract: Aim: To determine survival of infants with major congenital anomalies (CA) and assess the effect of co-existing anomalies and gestational age.Methods: All liveborn infants with major CA born in New South Wales (NSW), Australia, 2004Australia, -2009 were identified from the NSW Register of Congenital Conditions. Deaths were identified via record linkage to death registrations and five-year survival was estimated using Kaplan-Meier methods.Results: There were 8521 liveborn infants with CA of whom 617 (7.2%)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(39 citation statements)
references
References 30 publications
3
36
0
Order By: Relevance
“…Table 1 provides the description of 55 studies included in this review. Further detail on the sources of case ascertainment and death identification and the description of the comparison group, if any, are given in S4 Table. Nine studies analysed long-term survival of all congenital anomalies combined: seven with [6,8,15,17,[40][41][42] and two without [7,43] stratification by congenital anomaly group/subtype (Table 1). Other studies (n = 46) focused on specific groups or subtypes of congenital anomalies: the central nervous system (n = 5 [44][45][46][47][48][49]), including spina bifida [44][45][46]48,49] and encephaloele [44,47]; orofacial clefts (n = 1 [16]); anomalies of the digestive system (n = 22), including oesophageal atresia [9,50,51], anorectal malformations [52], congenital diaphragmatic hernia (CDH) [18,23,51,53,54], biliary atresia [36][37][38][39][55][56][57][58][59]…”
Section: Search Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Table 1 provides the description of 55 studies included in this review. Further detail on the sources of case ascertainment and death identification and the description of the comparison group, if any, are given in S4 Table. Nine studies analysed long-term survival of all congenital anomalies combined: seven with [6,8,15,17,[40][41][42] and two without [7,43] stratification by congenital anomaly group/subtype (Table 1). Other studies (n = 46) focused on specific groups or subtypes of congenital anomalies: the central nervous system (n = 5 [44][45][46][47][48][49]), including spina bifida [44][45][46]48,49] and encephaloele [44,47]; orofacial clefts (n = 1 [16]); anomalies of the digestive system (n = 22), including oesophageal atresia [9,50,51], anorectal malformations [52], congenital diaphragmatic hernia (CDH) [18,23,51,53,54], biliary atresia [36][37][38][39][55][56][57][58][59]…”
Section: Search Resultsmentioning
confidence: 99%
“…Survival in live births with anencephaly analysed by four studies was extremely low and varied from 0% [15,42] to 7.3% [40] by year 1 ( Table 2). Seven studies of survival in children born with spina bifida [6,15,[40][41][42]45,48] including 7,422 live births were summarised in a meta-analysis, with pooled survival estimates of 92%, 91%, 89%, and 88% at ages 5, 10, 20, and 25 years predicted for children born in 2020 (Table 3). Survival has improved significantly over time, with an increased OR per 10-year increase in birth year 1.34 (95% CI 1.24-1.46, p < 0.001) ( Table 3 and Fig 2).…”
Section: Congenital Anomalies Of the Nervous Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…The survival of infants with major congenital anomalies (CA) has improved in recent years. An Australian register‐based study by Schneuer et al showed that nine in 10 infants with major CA survived past 5 years of age, although survival rates varied across CA groups. Five‐year survival was higher for children with isolated anomalies than multiple anomalies and lower for preterm than term‐born infants.…”
Section: Five‐year Survival Rates For Major Congenital Anomalies Havementioning
confidence: 99%
“…Babies born with congenital abnormalities, generally, will be born as Low Birth Weight (LBW) Babies or small babies for their pregnancy age. Low Birth Weight Babies with congenital abnormalities that have a weight of about 20% die in the first week of life [18].…”
Section: The Risk Of Congenital Abnormalities To Perinatal Deathmentioning
confidence: 99%